Surgical Perspectives for Pediatric Theater Teams during the SARS-CoV-2 Pandemic and Beyond: Narrative Review and Mandatory Tasks Guidelines - Iacona, Roberta; Chima, Kiran; Kotecha, Ami; Saxena, Amulya (European Journal of Pediatric Surgery, 2021)
This is a narrative review during the ongoing coronavirus disease 2019 (COVID-19) pandemic to streamline workflow of pediatric surgical patients in operating theaters and for theater teams involved in their management. Pediatric patient anxiety in theaters, aspects of communication, and optimizing vision during surgery during the pandemic have also been addressed. The COVID-19 pandemic has led to the creation of pathways in the surgical management of patients. As the pandemic progressed, hospitals developed pathways to offer increased protection to staff during procedures. This narrative review provides a clear perspective in the management of pediatric patients in operating theaters. Guidelines received from National Health Authorities and Societies affiliated with surgery, endoscopic surgery, anesthesiology, and endoscopy were carefully reviewed regarding their recommendations and data emerging from reports on COVID-19 were selected to compile the pathways specific for pediatric patients and staff. The workflow pathways have been successfully implemented during the pandemic and include a section on patients for endoscopy as well as approach to endoscopic surgery and open procedures. Theater room ergonomics that were successful during the pandemic have been outlined along with identification of areas specific to the pediatric patient anxiety, interteam communication/identification, and visor-related vision. The guidelines used successfully during the pandemic for pediatric theater teams can be used or adapted for formulating local hospital guidelines in other centers that could be valuable in patient management beyond the pandemic.
Keywords: COVID-19; pediatric; theater teams; surgery; anesthesia; protection